1990
DOI: 10.21236/ada221939
|View full text |Cite
|
Sign up to set email alerts
|

Joint DoD/Industry Study on Opportunities in Integrated Diagnostics

Abstract: DEFINITIONSIDA publishes the following documents to report the results of its work. RepotRepots ae the most authoritatie and ost carefully considered products IDA Publishes. They normally embody results of major poject which (a) have a direct beaing on decisions affecting major programs, (b) address issues of slignificant Conc to the Eecutive Banch, the Conress andlor the public, or (c) address issues that have significant economic impficatns. IDA Reports ae rvewed by outside panels of experts to ensure their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We observed that current DoD MDC systems may highlight diagnostic problems but do not pinpoint the diagnostic improvements needed. This dramatically contrasts with commercial case studies previously evaluated at the Integrated Diagnostics Workshop in which the commercial systems were found to specifically emphasize identification and resolution of diagnostic and equipment problems [Brown, 1990].…”
Section: Comparison Of Observed Dod Practices With Commercial MDC Impmentioning
confidence: 57%
See 4 more Smart Citations
“…We observed that current DoD MDC systems may highlight diagnostic problems but do not pinpoint the diagnostic improvements needed. This dramatically contrasts with commercial case studies previously evaluated at the Integrated Diagnostics Workshop in which the commercial systems were found to specifically emphasize identification and resolution of diagnostic and equipment problems [Brown, 1990].…”
Section: Comparison Of Observed Dod Practices With Commercial MDC Impmentioning
confidence: 57%
“…We observed from the various MDC system program documentation that the justification and rationale for the individual programs focused on areas other than diagnostics accuracy improvement. We inferred from this that the synergistic processes used to improve diagnostic performance, similar to those found in the commercial case studies during the Integrated Diagnostics Workshop [Brown 1990], are not funded goals of the following programs.…”
Section: System Costsmentioning
confidence: 98%
See 3 more Smart Citations